Ternary Organic Solar Cell with 1750 h Half Lifetime Under Ultraviolet Irradiation with Solar Intensity. Issue 6 (7th March 2022) - Tran Ho, Ngoc Khanh; Liu, Chia-Chen; Chiu, Kuan-Yun; Meng, Hsin-Fei; Chao, Yu-Chiang; Li, Fenghong; Yu, Peichen; Zan, Hsiao-Wen; Horng, Sheng-Fu
Abstract : The ultraviolet (UV) radiation in the solar spectrum causes most of the decay under sunlight for solar cells based on organic photovoltaics (OPV). One‐year outdoor lifetime still remains challenging for OPV. The lifetime of 2000 h under continuous laboratory light corresponds to a 1 year outdoor lifetime. Herein, the stability of the OPVs is studied under continuous irradiation by a UV light emitting diode of 365 nm with a long tracking time. The intensity of 50 W m −2 is the same as the sunlight UV. The compositions of the active layer and cathode interfacial layer are sensitive to UV irradiation. In general, ternary devices have better UV stability than binary devices. In particular, a good stability is achieved for the ternary device based on the high‐performance blend with poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl‐3‐fluoro)thiophen‐2‐yl)‐benzo[1, 2‐b:4, 5‐b']dithiophene))‐alt‐(5, 5‐(1', 3'‐di‐2‐thienyl‐5', 7'‐bis(2‐ethylhexyl)benzo[1', 2'‐c:4', 5'‐c']dithiophene‐4, 8‐dione)] (PM6) as the donor. The acceptor is 2, 2'‐((2Z, 2'Z)‐((12, 13‐bis(2‐ethylhexyl)‐3, 9‐diundecyl‐12, 13‐dihydro‐[1, 2, 5]thiadiazolo[3, 4‐e]thieno[2", 3":4', 5']thieno[2', 3':4, 5]pyrrolo[3, 2‐g]thieno[2', 3':4, 5]thieno[3, 2‐b]indole‐2, 10‐diyl)bis(methanylylidene))bis(5, 6‐difluoro‐3‐oxo‐2, 3‐dihydro‐1H‐indene‐2, 1‐diylidene))dimalononitrile (Y6). The fullerene derivative [6, 6]‐phenyl C71 ‐butyric acid methyl ester (PC71 BM) is added as the second acceptor, whereas a polymer poly[(2, 6‐(4, 8‐bis(5‐(2‐ethylhexyl)thiophen‐2‐yl)benzo[1, 2‐b:4, 5‐b']dithiophene))‐co‐(1, 3‐di(5‐thiophene‐2‐yl)‐5, 7‐bis(2‐ethylhexyl)benzo[1, 2‐c:4, 5‐c']dithiophene‐4, 8‐dione)] (PBDB‐T) is added as the second donor. For the PM6:Y6 ternary device, the UV half lifetime is 1750 h, which is close to the 2000 h target set by the outdoor of a 1 year lifetime. Abstract : Herein, the ultraviolet (UV) stability with the solar intensity of solar cell based on organic photovoltaic is studied. The tracking time up to 2000 h is expanded. Non‐fullerene organic photovoltaics improves the UV stability by the device compositions. Ternary systems yield a UV half‐lifetime up to 1750 h which is close to 2000 h set by the outdoor lifetime of 1 year.